Affirming Verb Lexemes in A Practical Ndebele Dictionary and in Isichazamazwi SesiNdebele: The Case of -wa Verbs - Zondo, Jerry (Lexikos, 2009)
Abstract: Both A Practical Ndebele Dictionary (1971) by Pelling and Isichazamazwi SesiNdebele (2001) by Hadebe et al. lemmatize a number of -wa-ending verbs. Each one of the verbs is easily recognizable as a canonical or base form from which different word forms can be derived. Indeed they should all be seen as legitimate headwords that have been carefully selected for entry until a keener observation as presented in this article, questions the validity of the inclusion. It would be understood from both compilers that all the verbs entered are by virtue of their being legitimate verb bases. Since the verbs ending with -wa are canonical forms, they should be inflected with -iw-/-w-, the passive extension morpheme, and by any other extension morphemes. When -iw-/ -w- cannot inflect directly, the usual initial inflection to causative or applicative and then to passive should then apply. When -iw-/-w- cannot apply, it is likely that the headword in question is in fact a passive form already derived from another base form. The article argues that these words cannot claim to be legitimate headwords. The article further observes that other verb endings treated can be simi-larly tested and treated accordingly. Possibly headword selection will then be more consistent and charac-terized by a more considered and reasoned approach.